Ecosystem synergies as drivers of acquisitions - Burford, Natalie; Shipilov, Andrew V.; Furr, Nathan (Strategic Management Journal, 2025)
Abstract Research Summary We examine how the structure of ecosystems shapes firms’ acquisition choices. We develop a theoretical framework comprising three levels of ecosystem structure – local interdependence, clusters, and centrality – that could drive choices of M&A targets based on expected ecosystem synergies, a previously undocumented acquisition synergy that creates benefits for the acquirer and the ecosystem overall. Ecosystem synergy is value created through combination of the acquirer and target's ecosystem positions that improves the combined firm's alignment with third‐party complementors. Such synergies manifest themselves in increased attractiveness of the firms’ components to third parties by strengthening, attracting, or connecting complementarities. In the setting of the e‐commerce technology industry, our results show that firms acquire targets to increase local interdependence of their components and their presence in component clusters. Managerial Summary Innovation ecosystems are critical for firms’ performance. While prior research has established the importance of ecosystems and firms’ positioning within ecosystems, we do not actually know whether and how ecosystem structure shapes firms’ acquisition choices. In this article, we show that M&A targets are not chosen solely for the value created by the acquirer or target, but also for their broader ecosystem synergies. Ecosystem synergies are a previously undocumented acquisition synergy (distinct from internal synergies and market power) that manifest themselves in increased attractiveness of firms’ post‐acquisition components to third parties by strengthening, attracting, or connecting complementarities. We test our theory by mapping the ecosystem structure of 6187 technological components that drives 186 acquisitions in the e‐commerce technology sector during the period 2013 to 2021.